Cosmological model with fermion and tachyon fields - Akhmetova, G; Razina, O; Tsyba, P; Meirbekov, B (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article discusses a cosmological model with a fermion and tachyon field in four dimensions together with the homogeneous, isotropic and flat Friedmann-Robertson-Walker Universe. A system of equations of motion has been found for this model. Describe a power solution for the scale factor. Studied the energy conditions. The parameters that have been obtained satisfy the latest observational data for α > 1 . The pressure in the model under consideration is negative and tends to zero later. Found energy density and pressure, which correspond to the dark energy of the model under consideration, the energy conditions. The parameter of the equation of state ω , the deceleration parameter q , the jerk parameter j are found. Built graphics for the energy density ρ and pressure p , as well as for the equation of state parameter ω , deceleration parameter q and jerk parameter j .